Engineering Multifunctional Gold Decorated Dendritic Mesoporous Silica/Tantalum Oxide Nanoparticles for Intraperitoneal Tumor‐Specific Delivery. (27th February 2019) - Kashfi‐Sadabad, Raana; Gonzalez‐Fajardo, Laura; Hargrove, Derek; Ahmadi, Bahar; Munteanu, Daniel; Shahbazmohamadi, Sina; Jay, Michael; Lu, Xiuling
Abstract: Nonspecific high‐energy radiation for treatment of metastatic ovarian cancer is limited by damage to healthy organs, which can be mitigated by the use of radiosensitizers and image‐guided radiotherapy. Gold (Au) and tantalum oxide (TaO x ) nanoparticles (NPs), by virtue of their high atomic numbers, find utility in the design of bimetallic NP systems capable of high‐contrast computed tomography (CT) imaging as well as a potential radiosensitizing effect. These two radio‐dense metals are integrated into dendritic mesoporous silica NPs (dMSNs) with radial porous channels for high surface‐area loading of therapeutic agents. This approach results in stable, monodispersed dMSNs with a uniform distribution of Au on the surface and TaO x in the core that exhibits CT attenuation up to seven times greater than iodine or monometallic dMSNs without either TaO x or Au. Tumor targeting is assessed in a metastatic ovarian cancer mouse model. Ex vivo micro‐CT imaging of collected tumors shows that these NPs not only accumulate at tumor sites but also penetrate inside tumor tissues. This study demonstrates that after intraperitoneal administration, rationally designed bimetallic NPs can simultaneously serve as targeted contrast agents for imaging tumors and to enhance radiation therapy in metastatic ovarian cancer. Abstract : A new bimetallic nanosytem consisting of two radiodense elements, gold and tantalum oxide, is designed for high‐contrast computed tomography (CT) imaging with a potential radiosensitizing effect. This nanocomposite brings advantage of tumor accumulation after intraperitoneal administration to a metastatic ovarian cancer mouse model and offers 1.7–7.1 times higher CT contrast attenuation compared with monometallic configurations or clinically used iodine‐based agent.